Effect of Topical and Intravenously Applied Tranexamic Acid Compared to Control Group on Bleeding in Primary Unilateral Total Knee Arthroplasty - Uğurlu, Mahmut; Aksekili, Mehmet Atıf Erol; Çağlar, Ceyhun; Yüksel, Kağan; Şahin, Ercan; Akyol, Mesut (The Journal of Knee Surgery, 2017)
We aimed to answer the following three questions in this study: (1) Does tranexamic acid (TA) reduce the amount of bleeding in total knee arthroplasty (TKA)? (2) Does TA reduce requirement for blood transfusion? (3) Is there any difference on reliability and efficacy between topical and intravenous (IV) applications of TA? Patients were allocated into three groups randomly by a software program as topical, IV, and control group. TA was applied as 20 mg/kg to the IV group and as 3 g/100 mL saline to the topical group. The hemoglobin values were recorded preoperatively and postoperatively on the same day and on day 1 and day 2. Removal of the drain postoperatively and length of hospital stay, as well as any complications such as pulmonary embolism or deep venous thrombosis, were also noted. The study comprised 40 patients in the IV group, 42 in the topical group, and 41 in the control group. The drain output values were similar in the IV and topical groups (p = 0.161), while those of the control group were significantly higher than both the IV and topical groups (p < 0.001 and < 0.001). Transfusion was applied to 19.5% of cases in the control group, 4.8% in the topical group, and 5.1% of the IV group (χ2 = 6.522; p = 0.038). The results of the study showed that 20 mg/kg single-dose IV bolus or 3 g topical TA application reduced blood loss and transfusion requirement without increasing the rate of thromboembolic complications in unilateral primary TKA.
Keywords: tranexamic acid; total knee arthroplasty; topical; intravenous; hemoglobin